Climate change v Eurozone crisis: social and economic views of risk in inter-expert risk communication - Ou, P (2015)
This DPhil thesis discusses how two divergent risk conceptions, a 'social view' and an 'economic view' of risk, are constructed through inter-expert risk communication. Different and sometimes contradictory concepts of risk are mobilised in regulatory practice, but the origins of these divergent risk conceptions are not extensively studied. This thesis seeks to unpack this divergence. Empirically, I analyse risk communication among experts in the European Union (EU) during the creation of two risk regulation standards. The two case studies, one related to the development of the two-degree target of EU climate policies (the climate case) and the other about the negotiation of the excessive deficit criteria of the Maastricht Treaty (the euro case), can shed light on the relations between risk conceptions and inter-expert risk communication. I argue that through risk communication, an initial 'view' of risk can be entrenched and developed into a paradigmatic 'risk conception'. My analysis uses historical and sociological institutionalism, by focusing on path dependence of risk communication and social construction risk conceptions among EU experts. Through the two case studies, I identify four analytical dimensions of inter-expert risk communication: networks (the institutional setting and relationships between different experts), cultures (the mentalities of experts in relation to discussing risks), dynamics (the actual processes of transmitting and receiving risk messages) and strategies (the rationales supporting the decisions of risk regulation standards). My thematic analysis reveals four key distinct 'features' of social/economic views of risk: expertise (the types of knowledge mobilised), normality (characterising risk as either 'special' or 'routine'), probability (considering risk as either uncertain or calculable) and impact (seeing risk as either negative or positive). I argue that these four features can help explain the construction of risk conceptions, and more broadly, provide an analytical framework for studying how views of risk evolve and interact over time.